Pengaruh Besar Medan Magnet terhadap Pengurangan Kadar CaCO3 dalam Air - Triswantoro Putro; Endarko Endarko (JURNAL INTEGRASI, 2014)
The research on the influence of magnetic field over the CaCO3 precipitation in water has been carried out. The hard water is water contaminated with Ca2+, Mg2+, CO32-. Those ions are surrounded by water molecules which is also known as hydration shell. The hydration shell is a layer that holds ions to form a molecule such as a CaCO3. The given magnetic field will affect the hydration shell. The study was conducted by varying the magnitudes of the magnetic field which equal to 0.05 and 0.1 Tesla. The sample solution for this research is 520 mg/L CaCO3. The experiment has been accomplished within 120 minutes experiment resulted a maximum reduction percentage of 28.57% for the magnetic field value of 0.05 Tesla. While the magnetic field value of 0.1 Tesla obtained 57 ,69 % of the maximum reduction.